Photoredox-Catalyzed C(sp2)–H Bond Functionalization Reactions: A Short Account - Li, Jinling; Zhao, Junjie; Loh, Teck-Peng (Synlett, 2023)
Photoredox catalysis has been undergoing rapid development and wide application in the chemical community during the past several years because of its advantages for reaction engineering. Since 2016, Loh et al. started their research on photoredox-catalyzed reaction transformations, including β-C(sp2)–H fluoroalkylation, alkylation, and acylation of enamides, C(sp2)–H phosphorylation of alkenes converted from alcohols, C(sp2)–H bromination, and alkylation of (hetero)arenes. These transformations introduce a broad range of structural differences on the C(sp2)–H bond of compounds with an extensive array of functional groups and showcase the appealing synthetic utilities of the approach.1 Introduction2 Photoredox-Catalyzed β-C(sp2)–H Functionalization of Enamides3 Photoredox-Catalyzed C(sp2)–H Functionalization of Alkenes4 Photoredox-Catalyzed C(sp2)–H Functionalization of (Hetero)Arenes5 Conclusion
Keywords: photoredox catalysis; enamides; (hetero)arenes; alkenes; (fluoro)alkylation; acylation; bromination; phosphorylation